Perbandingan Taman Jepang Dan Taman Jawa - Budi Mulyadi (Diponegoro University, 2019)
(Title: Comparison Of Japanese Garden And Java Garden). The purpose of this paper is to find out the similarities and differences between Japanese garden and Java garden This research is research model that use literary review research model to collect the data. The paper shows that there are the similarities and differences between Japanese garden and Java garden. Seen from the concept Japanese Gardens do not recognize straight or symmetrical lines. Japanese gardens are deliberately designed asymmetric so that none of the elements become dominant while the Java garden concept is more concerned with beauty by planting many types of flowers that contain elements of philosophy seen from its elements, Japanese garden has 7 elements, namely water, stone, plants, water containers, bridges, sand and lanterns while the Java park has water elements, plants, buildings and organisms